Profil Mamalia Kecil Gunung Slamet Jawa Tengah - Maharadatunkamsi, Maharadatunkamsi (JURNAL BIOLOGI INDONESIA, 2011)
ABSTRACTProfile of Small mammals from Gunung Slamet, Central Jawa. Research of small mammals atGunung Slamet, Central Jawa was conducted. Three types of habitats as representation ofprimary forest, secondary forest and plantation were examined at Kalipagu, Kaliwadas andBambangan in order to record its small mammals biodiversity. Combination of trapping anddirect observation recorded 31 species of small mammals from the areas observed. Shannon-Wiener index was the highest in secondary forest (3.8) compared to primary forest (3.6) andplantation (3.4). The results indicated that most small mammals of Gunung Slamet use secondaryforest for their home range. However data on microchiropterans that were more frequentlyrecorded in plantations indicated that agricultural plants were their primary foraging areas. Onthe other hand, most of small mammals species were rely on both secondary forest and primaryforest as an important food resources. The dendogram resulting from cluster analysis wasconcordant with this view. Primary forest and secondary forest clustered closely together,while plantation was recognized as a distinct group.Key words: Small mammals, Gunung Slamet, biodiversity, habitat.